The Mesoscale Distribution Of Zooplankton Community In The Northeastern Pacific - Jung-Hoon Kang (International Marine Minerals Society, 2003)
Present study was stemmed from the survey associated with deep-sea mining in the KODOS area between Clarion Fracture Zone and Clipperton Fracture Zone located in the North Pacific Ocean. The study area, which is located in the southeastern part of North Pacific gyre, is oligotrophic waters with low nutrients and chl-a concentrations below 1µg/l (MOMAF, 1996). This area is also characterized by divergence at 8°N and convergence at 6°N, which moved northward or southward in the range of a few kilometers with seasonal and climate changes. If the waste materials related to deep-sea mining are intruded into the surface waters continuously, unexpected effects to water column ecosystem are anticipated negatively. In order to assess the impact on the planktonic ecosystem, natural variation need to be distinguished from anthropogenically induced variation in terms of the abundance and species composition of plankton. In this study, mesoscale variation of zooplankton community was reported in relation to the physical conditions in the northeastern Pacific during 1998 and 1999. Temperature and salinity were determined using a CTD from surface to 200m depth in July 3-20, 1998 and in June 22-July 1, 1999. Zooplankton samples were collected from two different depths (0-50m, 50-200m) by vertical towing using an opening-closing net (100cm diameter and 300 µm mesh size). The samplings were carried out at every one degree between 5° and 12°N (1998), between 5° and 11°N (1999) along the meridional lines of 131°30´ W. The net was lowered to the depth of interest from a stationary research vessel and towed upward to collect zooplankton at a speed of 25~30 m per minute. Zooplankton samples were transferred to 1-l sampling bottles and immediately fixed with neutralized formalin into the final concentration of 5%. Considering the characteristics of zooplankton such as diurnal vertical migration, all samplings were done during the nighttime. The volume filtered by the net was calculated from the readings of flow meter (Hydro-Bios Model 438-115). Zooplankton were identified to the genus level and enumerated under a microscope. The abundance of zooplankton at each station was expressed as the numbers/100 m3.